Perceived wage inequality, demand for wage equalization, and life satisfaction - Gábor Hajdu (Global Labor Organization (GLO), 2024)
This paper analyzes the relationship between perceived wage inequality, demand for wage equalization and life satisfaction. Using the large dataset of the Hungarian Microcensus of 2016 and a measure that quantifies perceived inequality based on respondents' wage estimates - rather than based on normative or attitudinal views or policy preferences, which are widely used in the literature - I find that individuals who perceive higher wage inequality and those who demand greater wage equalization tend to report lower life satisfaction. Furthermore, I show that the negative association between perceived wage inequality and life satisfaction is stronger among those who demand greater wage equalization. The results suggest that the association between perceived wage inequality and satisfaction is stronger for low SES respondents than for high SES respondents, but the latter appear to be more aware of the unfairness in income distribution.
Keywords: D31; D63; I31; 330; economic inequality; inequality perceptions; fairness; subjective well-being; life satisfaction